Analisa Dampak Lingkungan Terhadap Budidaya Tebu dengan Life Cycle Assesment Menggunakan OpenLCA 1.10.3 (Studi Kasus : Pabrik Gula Madukismo, Yogyakarta) - Elvis Umbu Lolo; Widianto Widianto; Richardus Indra Gunawan; Yonathan Suryo Pambudi; Alfred Dedu Ngalung (Jurnal Serambi Engineering, 2022)
The Madukismo sugar factory besides having a positive impact also has a negative impact on the environment, especially the sugarcane cultivation stage. Thus, prevention efforts are needed through saving energy and material use. Life cycle assessment is a method to identify environmental damage of an industrial process. The research only examines the sugarcane plantation process, so the scope of LCA is gate to gate with a functional unit of production of 1 ton of sugar cane in 2021. The results of the research are the use of sugar cane land of 0.246 ha, water 7177.057 m3, sugarcane seeds 0.531 kg and energy 173,999.43 MJ and environmental impacts of climate change (17035.15 kg CO2 Eq), acidification potential (77.4615 kg SO2 eq), eutrophication potential (65.33463 kg NOx Eq), human toxicity (13473.88 kg 1.4-DCB eq) and photochemical oxidation (3.729051 kg ethylene eq). Alternative improvement is the application of NPK, ZA, urea and organic fertilizers as well as herbicides that must be in accordance with the instructions of the Ministry of Agriculture in terms of the amount and duration of fertilizer application. The stage of cutting and transporting sugar cane is proposed by train, the consideration is that all sugar cane-producing areas are passed by rail. The next problem is the burning of open land after sugar cane harvest. With a large sugarcane area of 6318.11 ha, if burned, it will have an impact on the environment, the improvements made are by diverting post-harvest waste to replace the use of coal and wood in the sugar production process.